Factors perceived to contribute to the success of some selected school libraries - Sison, Gliceria C.; Hidalgo, Namnama P.; Picache, Ursula G. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1989)
The study aims to determine the following: 1) factors that are perceived to contribute to the effectiveness of school libraries; 2) the importance of these factors to the effectiveness of four selected grade school libraries in Metro Manila namely Ateneo, San Beda, Assumption, and St. Scholastica; and 3) whether school administrators, teachers and librarians differ in their perceptions of these factors in relation to their libraries.
The respondents of these study included 10 school administrators, 175 teachers, 12 librarians and 827 Grades 2-6 pupils. The survey method was used in this study. A questionnaire/checklist patterned after the Likert scale and the semantic differential technique was employed to gather data from school administrators, teachers and librarians. An opinionnaire was used to know the attitudes of the pupils about their school library. To gather data about the four schools' services, activities, and resources, interviews, visits, and observations were conducted.
The data from all respondents were tabulated and analyzed using simple frequency, means, standard deviation, Spearman rank-order correlation coefficient, one-way analysis of variance, and Scheffe's test.
The study identified from the library literature thirteen factors that contribute to the effectiveness of school libraries. These factors were confirmed by all the respondents. These factors, arranged in the order of importance as rated by the respondents, are the following: 1) adequate and accessible print and non-print materials, 2) qualified and trained professional staff, 3) cooperative media-minded faculty, 4) supportive media-minded administrators, 5) children's library-related activities, 6) well-developed long-range planning of library program, 7) library orientation program, 8) liberal funding, 9) systematic instruction to teachers in the use of library resources, 10) variety of specialized library personnel, 11) flexible scheduling, 12) cooperative parents, 13) participation of parents and volunteers in library activities.
The schools were rated Very Good on nine of these thirteen factors and of Great Importance on the other 4 factors. However, in regard to these factors that contribute to the effectiveness of the school library program in the four selected school libraries, the administrators, teachers and librarians differ in their ratings. The following are the eleven factors as the respondents ranked their school libraries in the order of their effectiveness: 1) print and non-print materials, 2) funding for the library, 3) children's participation in library activities, 4) support from media-minded administrators, 5) cooperation of library-minded faculty, 6) education and training of library staff, 7) planning of library program, 8) flexibility of library schedule, 9) instruction to teachers on use of library facilities, 10) cooperation, library-mindedness of parents, and 11) participation of parents and volunteers in library activities. The school libraries were rated Very Good in nine out of these eleven factors, while in the other two they were adjudged Good.
School administrators, teachers, and librarians were found to differ significantly in their ratings on four out of the eleven factors that contribute to their school library's effectiveness. The four factors are: a) education and training of library staff, b) planning of library program, c) flexibility of library schedule, and d) instruction to teachers on use of library facilities. Librarians tend to rate their school library on these four factors significantly higher than the school administrators and teachers. Lastly, pupils in the four schools showed very favorable attitudes toward their school library's activities and services.
The following are some recommendations for the four schools in this study: 1) Librarians should upgrade their education and training in order to come up with the expectations of the administrators, 2) there is a need to improve the system of instruction to teachers on use of library facilities, and 3) pre-service and in-service training of librarians as well as of school administrators should include observation or study of the programs of selected school libraries to serve as exemplers and models for emulaton.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Elementary school libraries -- Philippines -- Metro Manila; School libraries -- Activity programs